Destiny of the republic : a tale of madness, medicine and the murder of a president - Millard, Candice (New York : Doubleday, 2011)
A narrative account of the twentieth president's political career offers insight into his background as a scholar and Civil War hero, his battles against the corrupt establishment, and Alexander Graham Bell's failed attempt to save him from an assassin's bullet.
Includes bibliographical references (p. 313-323) and index.
Keywords: Garfield, James A. -- 1831-1881 -- Assassination; Guiteau, Charles Julius, -- 1841-1882.; Bell, Alexander Graham, -- 1847-1922; Garfield, James A. -- 1831-1881 -- Assassination; Guiteau, Charles Julius, -- 1841-1882.; Bell, Alexander Graham, -- 1847-1922; Presidents -- United States -- Biography; Presidents -- Medical care -- United States -- History -- 19th century; Medicine -- United States -- History -- 19th century; Medical instruments and apparatus -- United States -- History -- 19th century; Political culture -- United States -- History -- 19th century; Power (Social sciences) -- History -- United States -- 19th century; Presidents -- United States -- Biography; Presidents -- Medical care -- History; Medicine -- United States -- History; Power (Social sciences) -- United States -- History; United States -- Politics and government -- 1881-1885.; United States -- Politics and government